Antibacterial C-geranylflavonoids from Paulownia tomentosa Fruits - Smejkal, Karel; Chudík, Stanislav; Kloucek, Pavel; Marek, Radek; Cvacka, Josef; Urbanová, Marie; Julínek, Ondrej; Kokoska, Ladislav; Slapetová, Tereza; Holubová, Pavla; Zima, Ales; Dvorská, Margita (Journal of natural products, 2008)
Eight C-6-geranylflavonoids ( 1- 8) were isolated from an ethanol extract of Paulownia tomentosa fruits. Tomentodiplacone ( 1), 3'- O-methyl-5'-hydroxydiplacone ( 2), 3'- O-methyl-5'- O-methyldiplacone ( 3), and tomentodiplacone B ( 4) were obtained as new compounds, and 3'- O-methyldiplacol ( 5) was isolated for the first time from a natural source. The structures of these new compounds were determined by using mass spectrometry (including HRMS) and 1D and 2D NMR spectroscopy, and the absolute configurations of the compounds were determined by circular dichroism. The antibacterial activities of 1- 8 against seven bacteria and yeast were evaluated.
Keywords: flavonoidy; Microbial Sensitivity Tests; Flavonoids; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; Circular Dichroism; Plants, Medicinal; mikrobiální testy citlivosti; antibakteriální látky; molekulární struktura; Molecular Structure; cirkulární dichroismus; Scrophulariaceae; Anti-Bacterial Agents; Czech Republic; ovoce; Fruit; Candida albicans; Bacteria; Česká republika; léčivé rostliny